Crise hídrica: um estudo sobre o desempenho econômico financeiro das empresas brasileiras de saneamento diante de escassez de água - Almeida, Maria Donizeti Moraes (2016)
The objective of this research was to identify the economic importance of the consequences of the water crisis in revenue and business costs Brazilian sanitation sector. The research was delimited in publicly traded water companies with active registration in the CVM - Brazilian Securities Commission and was developed by collecting data from balance sheets published in the CVM, analysis of assessment methodologies and financial economic management indicators for companies’ services to present a result of increased reliability; research of the tariff structure from the sanitation companies. This research based on the economic and financial data of the company, consisting of multiple case studies from the period of 2011 to 2015, determining the year 2011 as parameter for the period (2012-2015) in which the level of rainfall was below expectations. Financial statements and management reports were analyzed, which demonstrated operating performance in revenues generation and the change in costs arising from services of the companies surveyed. The research noticed that of the 10 investigated companies, only two had solid situation in 2015 balance sheet, even with reduction revenue in the period of water scarcity. Seven had the average tariff of water supply and sewage service increased above the IPCA (inflation index) variation. The sad conclusion is that the resources obtained by the collection of tariffs are insufficient to maintain and expand the operational structure necessary to provide a quality service to the population and still remunerate the shareholders. Most of brazilian basic sanitation company are economically vulnerable to water instability